Teaching methods, facilities, and institutions in student ultrasound education (SUSE): e-learning, simulation, and ultrasound skills labs - Daum Nils; Schwanemann Jannis; Blaivas Michael; Prats Michael Ignacio; Hari Roman; Hoffmann Beatrice; Jenssen Christian; Krutz Alexander; Lucius Claudia; Neubauer Ricarda; Recker Florian; Sirli Roxana; et al. (Journal of Ultrasonography)
To acquire ultrasound skills, students need access to educational resources for both theoretical and practical knowledge. Effective training depends on the availability of educational content, training opportunities, and facilities – all of which are often scarce. E-learning platforms, simulation, and ultrasound skills labs are potential solutions to complement supervised real-life bedside training on patients and improve ultrasound education. This review discusses the advantages and disadvantages of e-learning, simulation, and ultrasound skills labs in the specific context of student education. E-learning platforms and teaching videos support students by offering flexible, accessible learning, allowing them to engage with material at their own pace. These digital resources complement practical lessons by providing essential theoretical knowledge that can be applied during hands-on sessions. Simulation creates a controlled environment for skill development and enhances patient safety, especially during interventional procedures. However, simulation equipment's high cost and technical complexity strain budgets and require specialized staff and training. Simulators often fail to replicate real-life variability, limiting skill transfer to patient care. The establishment of ultrasound skills labs offers a solid, long-term opportunity for skill retention but requires sufficient and sustainable funding. In conclusion, e-learning, simulation, and ultrasound skills labs can be valuable components of student ultrasound education if used deliberately. They should be included in a blended medical curriculum incorporating real-world clinical experiences to ensure effective transfer of learning to clinical practice.